Biogenic AgNPs—A Nano Weapon against Bacterial Canker of Tomato (BCT) - Asma Noshad; Mudassar Iqbal; Crispin Hetherington; Hassan Wahab (Advances in Agriculture)
Bacterial canker of tomato caused by the bacterial pathogen Clavibacter michiganensis subsp. michiganensis (Cmm) is a major limiting factor for tomato production worldwide. Currently there exists no resistant variety of tomato to bacterial canker; only cultural and chemical controls are available. This study synthesized AgNPs (silver nanoparticles) via a green chemistry route and investigated their bactericidal potential against bacterial canker of tomato (BCT). AgNPs were prepared using mycellial aqueous extract of agriculturally beneficial fungi Pythium oligandrum. The formation of AgNPs was confirmed by using UV–Vis spectroscopy for the absorbance pattern while their morphology was investigated by the transmission electron microscopy (TEM). The X-ray diffraction profile for the biogenic AgNPs confirmed a crystalline structure with an average particle size of 12 nm. AgNPs treated seeds showed a normal germination rate with normal seedling growth. An in-vitro study found that the prepared AgNPs caused the maximum inhibition of the bacterial pathogen. In the greenhouse the introduction of AgNPs significantly prevents and inhibits the bacterial pathogen Cmm on tomato plants. These results suggest that this process is a strong candidate for industrial scale production of AgNPs. These particles act as an inhibitor and broad spectrum antibacterial agent against cmm, and hence offer a new and eco-friendly alternative in BCT control.